ENSURING AIR SPACE CONTROL IN THE ACTIVITY OF THE STATE BORDER GUARD SERVICE OF UKRAINE: REGULATORY ASPECT - Філіппов, Станіслав Олександрович; Кушнір, Ірина Павлівна; Федорук, Михайло Віталійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
The purpose of the article is to develop proposals for improving the control of airspace as a component of the border security. Research methods: the use of the system-structural method and the method of generalization made it possible to identify general trends in the use of aircraft in border airspace for illegal purposes and identify related legal problems. By applying the formal legal method, ways to improve the legislation have been proposed. Results: as a result of the scientific search, the directions of regulatory and legal regulation in the field of air space control in the activity of the State Border Guard Service of Ukraine have been proposed. Discussion: the Armed Forces of Ukraine have the authority to control the airspace over a strip of the Earth’s surface running along the state border. At the same time, in modern conditions, illegal use of aircraft is widespread in the border area, which, due to their design features and weight, cannot always be detected by the Air Defense Forces of the Armed Forces of Ukraine. The main attention of the article is focused on the analysis of experience in protecting the state border of Ukraine, which demonstrates actual cases of detection of using such aircraft, which are mainly used near the state border for illegal purposes by the forces and means of the State Border Guard Service. That is why the article presents the results of a study of issues of legal support for control over the airspace of Ukraine as part of the activities of the State Border Guard Service of Ukraine. Also, in order to ensure the state border security, the proposals have been elaborated to counteract the illegal use of aircraft at the state border. In particular, in order to improve control over the airspace of Ukraine in the activity of the state border service of Ukraine it is proposed to: specify the list of objects and areas of the territory where unmanned aircraft flights are prohibited, which are under the protection and defense of the State Border Guard Service; grant authority to the bodies and divisions of the State Border Guard Service to exercise control over the airspace of the territories along the state border, technical capabilities for detecting and neutralizing UAVs; improve the procedure and rules for the use of aircraft (in particular, specify the rules for their registration, movement in controlled border areas), enhance responsibility for violations of the rules and their illegal use on and near the state border; enhance the interaction of bodies and divisions of the state border guard service with the Armed Forces of Ukraine, law enforcement agencies and public administration bodies on certain sections of the state border of Ukraine, with law enforcement agencies of neighboring countries on identifying and countering the illegal use of aircraft on the state border; increase the fleet of modern aircraft with high technical characteristics (aircraft, navigation and lifting), as well as other means used by the State Border Guard Service to effectively combat the illegal use of UAVs. This should be provided for in counteraction programs, especially when forming a budget for the purchase of equipment, the characteristics of which should be better than that used by offenders.